Meaning and Interpretation Wittgenstein, Henry James, and Literary Knowledge - Hagberg, G. L. (Cornell University Press, 2018)
'What is the meaning of a word?' In this thought-provoking book, Hagberg demonstrates how this question-which initiated Wittgenstein's later work in the philosophy of language-is significant for our understanding not only of linguistic meaning but of the meaning of works of art and literature as well.